SOUTH BORNEO ROWING SPORT VENUE - Simanto, Patrisius Steven; Aufa, Naimatul (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2022)
South Borneo often to take a part in rowing sport competitions starting from local, national, to international class. South Borneo rowing athletes have potency to compete in national into international competition and reach medals that became the pride of South Borneo Province. However, that situation isn’t match with adequate training facility and coaching so that the athlete’s potency is not supported by the coaching situation. South Borneo Rowing Sport Venue is designed with a purpose to fulfill the athlete’s coaching function to be professional athletes from South Borneo. Through Kayuh Baimbai concept program and symbolic architecture method that inspired from dragon boat, this venue is expected to create sense of enthusiasm, motivation, and the meaning of relationship between rowing sport and nature in athletes and South Borneo citizen through physical and non physical setting in rowing sport venue that can realize sustainability in South Borneo rowing sport.